Factors Affecting the Farming System of Gwaltar (Sindhuli) and Birta (Ramechhap) Village, Nepal - Lama, Sunita; Baral, Chandra Kanta (The Geographic Base, 2022)
Farming in Nepal is subsistence-based and is mostly integrated with livestock. Farming is seasonal and weather dependent. Different factors of agricultural system such as soil, water, livestock, labor, climate change and other resources within a given environment have affected farming. Primary data was collected using the tools like household survey, key informants’ interview, focus group discussion and field observations. In order to select the households for the household questionnaires, a random sampling technique was carried out. The study area consists of two villages viz. Birta and Gwaltar divided by a Sunkoshi River, Gwaltar having wet land on the other hand, Birta having dried land and thus 30 households from each village were selected. Despite of lying the village in the same region, there is variation in the selection of crops, cropping pattern and amount of production. It has found that policy, infrastructure, market, lack of irrigation water, climate change etc. are some of the major constraints for Birta while these factors affecting the farming in Gwaltar was less. Water scarcity in Birta was increasing, affecting the agricultural production and resulting in food insecurity. They were accessed to limited irrigation, low income level, limited institut.ional capacity resulting these effects in crop types, production, household food security and household income.